(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This is the report of a trajectory of approximation to the Huni kuĩ people through relational aesthetics, with the objective of supplying a scarcity of traditional knowledge in formal spaces of education. To enrich the encounter of alterities, there was the reflexive process “Theatre with the forest”, aiming to enhance the theatrical event through an ecological perspective. Three axes emerged from this process: the public, the sociality, and the space. As a practical means of this search, the theatre by João Redondo and the theatre by Lambe-Lambe were used within the traditional environment of the community, the forest. The main authors mobilized were Nicolas Bourriaud (2009), André Carreira (2009, 2013), Els Lagrou (2002, 2010) and Fritjof Capra (1997).